Optimal concentration of organic solvents to be used in the broth microdilution method to determine the antimicrobial activity of natural products against Paenibacillus larvae - Cugnata, Noelia Melina (2017)
American Foulbrood (AFB) is a bacterial disease, caused by Paenibacillus larvae, that affects honeybees (Apis mellifera). Alternative strategies to control AFB are based on the treatment of the beehives with antimicrobial natural substances such as extracts, essential oils and/or pure compounds from plants, honey by-products, bacteria and moulds. The broth microdilution method is currently one of the most widely used methods to determine the minimum inhibitory concentration (MIC) of a substance. In this regard, the fact that most natural products, due to their lipophilic nature, must be dissolved in organic solvents or their aqueous mixtures is an issue of major concern because the organic solvent becomes part of the dilution in the incubation medium, and therefore, can interfere with bacterial viability depending on its nature and concentration. A systematic study was carried out to determine by the broth microdilution method the MIC and the maximum non inhibitory concentration (MNIC) against P. larvae of the most common organic solvents used to extract or dissolve natural products, i.e. ethanol, methanol, acetonitrile, n-butanol, dimethylsulfoxide, and acidified hydromethanolic solutions. From the MIC and MNIC for each organic solvent, recommended maximum concentrations in contact with P. larvae were established: DMSO 5% (v/v), acetonitrile 7.5% (v/v), ethanol 7.5% (v/v), methanol 12% (v/v), n-butanol 1% (v/v), and methanol-water-acetic acid (1.25:98.71:0.04, v/v/v).